Impact of smoking on the response to treatment of thyroid associated ophthalmopathy. Issue 6 (1st June 2003) - Eckstein, A; Quadbeck, B; Mueller, G; Rettenmeier, A W; Hoermann, R; Mann, K; Steuhl, P; Esser, J
Abstract : Background: In patients with Graves' disease, smoking considerably increases the incidence and severity of thyroid associated ophthalmopathy (TAO). The authors sought to determine if smoking also influences the course of TAO during treatment, and the efficacy of therapy. Methods: 41 smokers and 19 non-smokers with moderate untreated TAO were included in this prospective study. All patients were treated with steroids and, 6 weeks after the beginning of drug therapy, with orbital irradiation. Follow up was performed 1.5, 4.5, 7.5, and 12 months after the beginning of the study. Proptosis, clinical activity score (CAS), and motility were evaluated. The extent of smoking was derived from the concentration of the haemoglobin adduct N -2-hydroxyethylvaline (HEV), a parameter of long term smoking. Results: There was no difference in the clinical manifestations of TAO between smokers and non-smokers at the beginning of treatment. However, CAS decreased (p<0.05) and motility improved (p<0.02) significantly faster and to a greater extent in non-smokers than smokers. Inverse correlations between the CAS decrease and the HEV levels observed 4.5 and 7.5 months after the beginning of treatment and between the improvement of motility and the HEV levels after 1.5, 4.5, and 7.5 months indicated a dose dependence. Mean HEV levels did not vary much during the follow up period and were significantly different in smokers (mean 5.4 (SD 2.7) μg/l) and non-smokers (mean 1.8 (1.3) μg/l; p<0.01). Conclusion: Smoking influences the course of TAO during treatment in a dose dependent manner. The response to treatment is delayed and considerably poorer in smokers.